HIV/AIDS dan Dampaknya Terhadap Produktivitas Kerja di Perusahaan X - Dimas Alyuda Pratama (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
HIV/AIDS can be a threat to the Indonesian workforce and have a devastating impact on the economy and problems at the workplace. Various negative impacts that arise as a result, HIV/AIDS infection, such as people in pain, less productive work, and even death. The writing of this literature review is to explain the impact of HIV/AIDS in enterprises on labor productivity. Literature review is an important part of research that narrates the relevant literature on HIV/AIDS in companies and its impact on labor productivity through a search of various literature sourced from google scholar. Literature search that has been carried out from the search for articles obtained information that workers suffering from HIV/AIDS will experience economic losses and lose their jobs. Other impacts in the form of an illness and even death will be felt by the workforce with HIV/AIDS status. The company will spend quite a lot in handling the cost of treatment and care as well as the rehabilitation of the status of HIV/AIDS employees. In addition to additional health problems that can increase the adverse impact on work productivity to affect the quantity or quality of production and have a significant impact on the national economy. Various negative impacts resulting from the workforce infected with HIV / AIDS include direct and indirect economic losses to the supply of workers, companies, and the state.